The Dynamics of Terminal and Instrumental Values of Education on the Example of MGIMO Students - A. L. Temnitskiy (Vestnik MGIMO-Universiteta)
Attitude towards derivable knowledge as a process of satisfaction of cognition needs and also as opportunity for developing flairs and making self-improvement can be called terminal. At the same time, the increase of pragmatism in society and in demands of employers for graduates doesn't stimulate students' interest in terminal values of education. Nowadays students become much more interested in receiving good marks and good exam results than in the matter of subject that they study; they become more attracted by an opportunity of having a good time in university and making helpful acquaintances than by a chance of making a professional self-determination. How spread is the instrumental students' attitude towards studying at the university? Is it possible that under the influence of this phenomenon the terminal values of education may be extruded? These and other questions are being examined on the base of materials of four recurrent sociological researches carried out among MGIMO students in 2001-2013. The main objects of analysis are the values of educational process, relations with fellow-students, essential qualities of lecturer's personality, ways of spending free time. It was found out that the terminal educational values predominate among MGIMO students. They study a lot, tensely and with enthusiasm, spending the modal part of time doing their homework, actively working on their self-improvement. It is revealed that intimate knowledge and self-improvement as 2 main terminal values in education assign multidirectional vectors towards different aspects of educational process.